Zhen-wu-tang ameliorates adenine-induced chronic renal failure in rats: regulation of the canonical Wnt4/beta-catenin signaling in the kidneys. (12th June 2018) - La, Lei; Wang, Lili; Qin, Fei; Jiang, Jian; He, Songqi; Wang, Chunxia; Li, Yuhao
Abstract: Ethnopharmacological relevance: Zhen-wu-tang ( ZWT ), composed of Radix Aconiti lateralis, Rhizoma Atractylodis macrocephalae, Poria, Radix Paeoniae alba and ginger, is a classic Chinese herbal formula for the treatment of chronic kidney diseases that may cause chronic renal failure (CRF). Aim of the study: To better understand its clinical use, this study investigated the effects and underlying mechanisms of action of ZWT on CRF. Materials and methods: CRF was induced by adenine. ZWT was given via an oral gavage method. The serum biochemical parameters were measured enzymatically or by ELISA. The kidneys were examined pathohistologically. The gene expression was analyzed by real time PCR and Western blot. Results: Similar to the positive control losartan, ZWT extract inhibited adenine-induced increase in serum concentrations of creatinine, BUN and advanced oxidation protein products in rats. These effects were accompanied by attenuation of proteinuria and renal pathological changes and suppression of renal mRNA and protein overexpression of Collagen IV and fibronectin, two of the key components of fibrosis. Mechanistically, renal mRNA and protein expression of Wnt4, a Wnt signaling ligand, was increased in the adenine-treated group, compared to the vehicle-treated control. Consistently, Wnt4 downstream genes beta-catenin and Axin were also overexpressed. Treatment with ZWT extract and losartan suppressed adenine-stimulated overexpression of these mRNAs and proteins. Conclusions: The present results demonstrate that ZWT extract ameliorates adenine-induced CRF in rats by regulation of the canonical Wnt4/beta-catenin signaling in the kidneys. Our findings provide new insight into the underlying renoprotective mechanisms of the ancient formula. Graphical abstract: fx1